Bajau's Tekodon: A Preliminary Study - Asmiaty Amat; Lokman Abdul Samad (Ricthmann Publishing, 2013)
Riddle is a form of oral literature that is very popular in Malaysia. Amongst the different ethnic groups in Sabah, ownership of riddles are identified by their ethnic origins. The ‘sundait’ is the riddle of the Kadazandusun, the ‘antuka’ of the Iranun, and the ‘tekodon’ of the Bajau. Riddle is a poem in question format, which is meant for guessing. It also creates a sense of togtherness in the rural community. Tekodon has developed among the Bajau community living in the rural areas in Kota Belud on the West Coast of Sabah. The Bajau’s ‘tekodon’ has forms and themes similar to Malay riddles in Peninsular Malaysia.